Mengestimasi Dampak Ekonomi Dari Kasus Pelarian Modal Di Indonesia - Muhammad Akbar Ramadhani; Erissa Nilasari; Abdul Haris (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
Indonesia faces a capital flight problem that fluctuates throughout the year, which could further affect the decline in Indonesian economic performance. The aim of the research was to test the relationship of capital flight with economic aspects such as national income, foreign debt, and tax revenues from 1990-2022. The estimates using the Vector Error Correction Model (VECM) model. The VECM estimates show that only the national income variables with a short-term and long-term relationship, the Granger causality test, informs there is no two-way causality relationship, and there is only a one-way causality relationship. The IRF and FEVD tests show that capital escape results in an increase in Indonesian foreign debt even though foreign debts eventually remain well-managed; on the other hand, capital evasion reduces national income and weakens the tax base in Indonesia because capital escapes are also in the form of tax evasion. Governments need to create economic stability to prevent capital evasion and improve tax compliance to avoid the widespread tax avoidance and evasion practices that lower tax revenues.